Trends in the Use of Project-Based Learning Model LKPD to Improve Learners' Science Literacy: A Bibliometric Analysis (2015-2025) - Muhammad Tantawi Jauhari; Ahmad Harjono; A. A Sukarso (Balai Publikasi Indonesia, 2025)
This study presents a bibliometric analysis of the trend in the use of Learner Worksheets (LKPD) based on the Project-Based Learning (PjBL) model to improve students' science literacy. The main objective of this research is to identify and analyze annual publication trends, disciplinary focus, and major thematic clusters in this research domain from 2015 to 2025. Data was collected from Google Scholar via Publish or Perish and Dimension.ai, with procedures adapted from PRISMA guidelines, and analyzed using VOSviewer software. The results showed a significant increase in the number of publications, signaling the field as a rapidly growing research frontier. The dominance of the ‘Education’ category was complemented by substantial contributions from ‘Information and Computer Science’ and ‘Engineering,’ indicating a shift towards technology integration. Thematic clusters confirmed the close relationship between PjBL, LKPD, and science literacy, with an emphasis on problem-solving and STEM-based development. PjBL proved effective in improving science literacy and collaborative skills, although implementation challenges such as time management and teacher competence still exist. The findings provide valuable insights for educators, curriculum developers, and policymakers to optimize the implementation of PjBL in science education